2019
DOI: 10.3390/geosciences9030128
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Neoformations on Modern Buildings and Engineering Structures in Tyumen City, Russia: Structural Features and Development Factors

Abstract: The paper presents the results of studying the development of calcite neoformations on the surfaces of modern buildings within the city of Tyumen. The objects of the study were carbonate crusts and stalactite-like bodies formed on the surfaces of five representative buildings in the city center. Research methods included visual diagnostics, optical microscopy, scanning electron microscopy with energy dispersive X-ray spectroscopy, confocal laser scanning microscopy and semi-quantitative determination of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…The layer varies between 30-90 μm, which is in good agreement with other literature report [39]. By brushing, the layer is thickened, as SEM images shown (Figure 10a-d).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The layer varies between 30-90 μm, which is in good agreement with other literature report [39]. By brushing, the layer is thickened, as SEM images shown (Figure 10a-d).…”
Section: Discussionsupporting
confidence: 91%
“…The layer thickness of the other consolidants is very thin, between 8-10 μm, this being a possible reason for the low efficacy of them. The layer varies between 30-90 µm, which is in good agreement with other literature report [39]. By brushing, the layer is thickened, as SEM images shown (Figure 10a-d).…”
Section: Discussionsupporting
confidence: 91%
“…Field observations are a characteristic, distinguishing method in geological studies and previously I have alluded to the example of how Lyell [6] highlighted the importance of field observations in refuting Werner theory about the genesis of igneous rocks. The paper presented in this special issue by Novoselov et al [12] presents extensive field studies asserting the frequency and diversity of carbonate neoformations but goes significantly further with laboratory studies that show how studies in the built environment can contribute to the discussion of some fundamental issues of geosciences (in this case, mineral genesis). The hypothesis proposed by the authors on the biological contribution must be highlighted given the present interest in biomineralization, namely of calcium carbonate.…”
mentioning
confidence: 95%
“…Indeed, one can argue that in the same way that there are patterns of speciation specific for organisms in the urban environments [11], there are undesigned crystal-forming processes that could be specific to the urban environment. The interactions between building materials and weathering agents contribute to the formation of products that are chemically and structurally similar to mineral species found outside the built environment, and the paper by Novoselov et al [12] presents a very detailed study of carbonate neoformations. My research has also involved this kind of products and indeed in a 2017 publication [13] based on extensive field observations, we concluded that they were the most extensive alteration feature in recent structures as they can occur in outside and inside places (some underground stations of Lisbon and Porto Metro systems in Portugal present easily observable examples).…”
mentioning
confidence: 99%
See 1 more Smart Citation